Validation of Appendicitis Inflammatory Response (AIR) Score and Alvarado Score - Haider, Tusneem; Naveed, Asad; Amjad, Fatima; Kamran, Ch. Muhammad; Amjad, Tahreem (Biological and Clinical Sciences Research Journal, 2025)
The scoring systems used for the diagnosis of acute appendicitis, such as the Alvarado score and the appendicitis inflammatory response score, are used for the accurate diagnosis as well as for preventing negative appendectomies. Objective: To validate these scores in the case of acute appendicitis. Methodology: This was a cross-sectional study conducted among patients enrolled from the Emergency Department of General Surgery at Jinnah Hospital, Lahore, from August 16, 2024, to February 15, 2025, with suspected acute appendicitis. A questionnaire was completed after taking a proper history, examination, and laboratory investigations, calculating the AIR and Alvarado scores, and receiving the histopathology report of the specimen. Based on the data collected, sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy were calculated for each scoring system separately. Results: Alvarado score was positive (>6) in 73.8% of the appendectomies, while negative in 26% appendectomies. The AIR score was positive (>4) in 76.9% of the appendectomies, while negative (<4) in 23.1% of the appendectomies. Almost 77.5% of appendectomies turned out to be positive on histopathology. The sensitivity of the Alvarado score was 89.5%, while that of the AIR score was 96.7%. The specificity of the Alvarado score was 80.55% while that of the AIR score was 91.6%. The PPV of the Alvarado score was 94.1% while that of the AIR score was 97.56%. The diagnostic accuracy of the Alvarado score was 87.5% while that of the AIR score was 95.6%. Conclusion: A positive AIR score is more specific and sensitive than a positive Alvarado score in accurately diagnosing acute appendicitis.